Efficacy of High Tibial Osteotomy in the Treatment of Medial Compartment Osteoarthritis: A Systematic Review - Andriessanto C. Lengkong; Stefan A.G.P Kambey (Eduvest - Journal of Universal Studies, 2024)
Osteoarthritis of the medial compartment of the knee is one of the common degenerative diseases among the adult population, causing chronic pain, stiffness, and limited joint function. High Tibial Osteotomy (HTO) has become an important treatment option to address deformity and reduce symptoms in patients with varus osteoarthritis. Objectives: This study aimed to conduct a systematic review of the existing literature to evaluate the efficacy of High Tibial Osteotomy in the treatment of osteoarthritis of the medial compartment of the knee. A literature search was conducted through PubMed, Google Scholar, and Cochrane Library databases for studies that met the inclusion criteria. Clinical outcomes, including improvement in pain, joint function, and radiological changes, were extracted and synthesized to provide a comprehensive picture of the efficacy of HTO. The results of the systematic review showed that High Tibial Osteotomy significantly reduced pain, improved joint function, and slowed disease progression in most patients with osteoarthritis of the medial compartment of the knee. Despite variations in surgical technique and reported clinical outcomes, HTO is generally considered an effective and sustainable procedure in the management of varus osteoarthritis. High Tibial Osteotomy shows strong promise as an important treatment option for patients with medial compartment osteoarthritis of the knee. However, it is important to take into account individual patient characteristics and consider additional therapies to maximize long-term outcomes. Further research is needed to deepen our understanding of this technique and to optimize its benefits in the treatment of osteoarthritis.